Audits of emergency trolleys' contents in selected hospitals in Botswana - Lakshmi Rajeswaran; Valerie J. Ehlers (AOSIS, 2012)
Cardiac arrest is a life-threatening emergency situation. The outcome depends on timely and effective cardio-pulmonary resuscitation (CPR). Successful CPR attempts in hospitals require well-equipped emergency trolleys and properly functioning equipment, as well as staff members skilled in performing CPR. The study aimed to determine whether the emergency trolleys in Botswana's hospitals' wards or units met the expected standards. The contents of the emergency trolleys in 20 wards or units of two referral government hospitals in Botswana were audited by using a standardised checklist. No hospital ward or unit had all the expected equipment or drugs on its emergency trolley, some units failed to check their emergency trolleys' contents daily. All 20 hospital wards or units that participated in this study, needed to improve the contents and maintenance of their emergency trolleys, otherwise in-hospital CPR efforts in Botswana might be doomed to failure, losing lives that could have been saved if emergency trolleys' equipment and supplies had been up to standard. Opsomming Hartarres is 'n lewensbedreigende noodsituasie. Die uitkoms word bepaal deur tydige en effektiewe kardio-pulmonale resussitasie (KPR). Suksesvolle KPR pogings in hospitale vereis goed toegeruste noodtrollies en toerusting wat behoorlik funksioneer, asook personeellede wat bedrewe is in die uitvoering van KPR. Die studie het gepoog om te bepaal of die noodtrollies in Botswana se hospitaalsale of eenhede aan die verwagte standaarde voldoen. Die inhoud van die noodtrollies in 20 sale of enhede van twee van Botswana se hospitale is ge-ouditeer deur 'n gestandardiseerde kontrolelys te benut. Geen hospitaalsaal of eenheid het al die verwagte toerusting of drogerye op sy noodtrollie gehad nie, sommige eenhede het nie hulle noodtrollies se inhoud gereeld gekontroleer nie. Al 20 hospitaalsale of eenhede wat aan die studie deelgeneem het, moet die inhoud en instandhouding van hulle noodtrollies verbeter, anders kan in-hospitaal KPR pogings in Botswana tot mislukkings gedoem wees, waardeur lewens verloor word wat gered kon gewees het, indien die noodtrollies se inhoud op standaard was.